USE OF KDAM COMPUTER PROGRAM MODULES FOR DYNAMIC ANALYSIS OF THE BATTAN MECHANISM IN THE FORMATION OF MULTI-LAYER FABRICS - SHCHERBAN, VOLODYMYR; VOLIANYK, OLEKSII; GOLDBERG, MARJANA; MELNIK, GENADIJ; SHCHERBAN, YURYJ (Herald of Khmelnytskyi National University. Technical sciences, 2024)
In the work, using the KDAM computer program module, a dynamic analysis of the batten mechanism of a heavy loom in the production of multilayer technical fabrics was carried out. The computer module allows you to determine the projections and full reactions in the hinges of the batten mechanism at the time of the weft thread surf in the zone of formation of multilayer fabrics, taking into account the structure of protective layers, main power layers and the method of connecting layers to each other. The influence of the structure of multilayer fabrics on the magnitude of dynamic reactions in the hinges of the batan mechanism was established.Multi-layer technical fabrics are used for the production of power grabs for laying pipes of oil and gas pipelines. Pipes are delivered with factory insulation. These fabrics have a high density of the main threads in the cross section of the power grip. The main thread system consists of the warp threads of the protective layers, the warp threads of the power layers, and the warp threads that bind the layers together. The formation of an element of multilayered technical fabric takes place by wefting the weft thread in the working area. Taking into account the very significant tension of the threads of the base, the strength of the surf can reach significant indicators. In the process of surf, there is a shock impact on the batting mechanism of the weaving loom. The resulting dynamic reactions in the hinges need to be evaluated, namely how the structure of multilayer fabrics affects the magnitude of the dynamic reactions in the hinges of the baton mechanism. Changing the structure of the multilayer technical fabric allows to reduce the tension of the base of the protective layers and power layers, which will lead to a decrease in the magnitude of the surf force and, as a result, to a decrease in dynamic reactions in the hinges of the batten mechanism. This will significantly reduce the wear in hinge pairs and increase the durability of the mechanism.To solve the complex task of dynamic analysis of the batting mechanism during the formation of multilayer fabrics, it is necessary to use specialized software complexes. The use of special computer modules allows you to determine the projections and full reactions in the hinges of the batting mechanism at the moment of the weft thread in the zone of formation of multilayer fabrics, taking into account the structure of protective layers, main power layers and the method of connecting the layers together.
Keywords: module; computer program KDAM; dynamic analysis; batan mechanism; multilayer fabrics